PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS, CAKUPAN OPERASIONAL PERUSAHAAN, DAN SERTIFIKASI ISO 14001 TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012-2013) - Bawono, Adetya Agung Kusumo; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2015)
This study aims to test empirically the effect of firm size, leverage, profitability, operational scope of the company, the certification of ISO 14001 on the disclosure of corporate social responsibility in manufacturing companies in Indonesia. Samples were taken by using purposive sampling then selected with predetermined criteria and obtained a sample of 192 companies. This study uses secondary data, annual report manufactur companies listed in Indonesia Stock Exchange 2012-2013. Data analysis techniques used in this research is multiple linear regression analysis technique. The results showed that the variable size of the company and ISO 14001 certification has a positive significant effect on the disclosure of corporate social responsibility. While variable leverage, profitability, and operational coverage th```e company has no significant effect on the disclosure of corporate social responsibility.